Trauma center vs. nearest non-trauma center: direct transport or bypass approach for out-of-hospital traumatic cardiac arrest - Ming-Fang Wang; Chen-Bin Chen; Chip-Jin Ng; Wei-Chen Chen; Shang-Li Tsai; Chien-Hsiung Huang; Chi-Yuan Chang; Li-Heng Tsai; Chi-Chun Lin; Cheng-Yu Chien (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Out-of-hospital traumatic cardiac arrest (TCA), a sudden loss of heart function caused by severe trauma such as blunt, penetrating, or other injuries, presents significant public health challenges due to its high severity and extremely low survival rates. Approximately 2.7% of trauma patients experience cardiac arrest at the scene, with an overall survival rate of less than 5%. The correlations of prognosis with various transport approach, such as hospital level with different distance, are yet to be clarified. Thus, we conducted this study to assess the association of transporting TCA patients to hospitals of different levels and distances on critical outcomes, including the return of spontaneous circulation (ROSC), survival to admission, and 30-day survival. Methods This retrospective study included adults with TCA who were admitted to various emergency departments in Taoyuan City between January 2016 and December 2022. The patients were stratified by destination hospital into three groups: those transported to a trauma center (TC; TC group), those transported to the nearest non-TC (non-TC group), and those cross-regionally transported to a TC (cross-region TC group). Geographic information system (GIS) data were utilized to determine hospital locations and distances. The associations between various factors and key outcomes—any return of spontaneous circulation (ROSC), survival to admission, 24-h survival and 30-day survival—were analyzed. Multivariable logistic regression was used to determine the association of these outcomes based on transportation to hospitals of different levels. Results This study included 557 patients with TCA (TC: 190 [direct transport: 72; cross-region transport: 118]; non-TC: 367). The TC and cross-region TC groups demonstrated significantly higher rates of ROSC at 30.6% and 30.5%, respectively, as well as lower mortality rates (95.8% for both), compared to the non-TC group, which had a ROSC rate of 12.0% and a mortality rate of 99.5%. Multivariable analysis revealed significant associations between favorable outcomes and transportation to a trauma center, either directly (aOR 2.91, 95% CI 1.54–5.49) or via cross-region transfer (aOR 2.05, 95% CI 1.01–4.15). Furthermore, blunt trauma was significantly associated with a poorer survival prognosis (aOR 0.31, 95% CI 0.08–0.78). Discussion This study highlights the positive associations of direct or cross-region transportation to a TC on the outcomes of TCA. Our findings challenge the current EMT transport approach in Taiwan, which prioritizes transporting TCA patients to the nearest hospital regardless of its level, potentially leading to worse outcomes. Transport time and TC distance may not significantly influence prognosis. Conclusion Bypassing and directly transporting to a TC within the observed (10 km) distances are associated with better survival rates in patients with TCA. Furthermore, blunt TCA is associated with a poorer survival prognosis compared to other mechanisms of trauma-induced cardiac arrest.